2016
DOI: 10.1002/slct.201600992
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Derivatization of Curcumin and its Effect on Antioxidant Capacity and Action Mechanism. Cyclic Voltammetry and DFT as Tools of Analysis

Abstract: Eight curcumin derivatives were synthesized by esterification of its phenol groups with first and second generation polyester dendrons (dendronization) or glutaric anhydride (glutarization), in a systematic scheme where mono and disubstitutions were carried out. The dendronization of curcumin (CUR) affects the fragmentation patterns in mass spectra, particularly for the disubstituted OH-terminated second generation derivative (labeled as 2C2), undergoing the cleavage of one of the aromatic rings. This fact may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Another study reported the exploitation of the CV and MS measurements, as well as DFT calculations to assess the reactivity of mono-or di-substituted CU derivatives, obtained by esterification with first-and second-generation polyester dendrons and glutaric anhydride, towards the electrogenerated superoxide anion. All tested compounds presented AOC, demonstrated by their reaction with O2 ▪− , which followed a PT mechanism excepting the disubstituted OH-terminated second-generation derivative, for which the mechanism was based on HAT reactions [124].…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…Another study reported the exploitation of the CV and MS measurements, as well as DFT calculations to assess the reactivity of mono-or di-substituted CU derivatives, obtained by esterification with first-and second-generation polyester dendrons and glutaric anhydride, towards the electrogenerated superoxide anion. All tested compounds presented AOC, demonstrated by their reaction with O2 ▪− , which followed a PT mechanism excepting the disubstituted OH-terminated second-generation derivative, for which the mechanism was based on HAT reactions [124].…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43] Polyester dendrimers and dendrons derived from 2,2′-bis(hydroxymethyl)propionic acid (bis-MPA) have gained singular attention related to their high aqueous solubility because of their hydroxyl groups in the periphery, that in turn, induced biocompatibility, and hydrolytic degradability. 44,45 These dendrons have used to enhance the aqueous solubility of curcumin by ester linkage 46,47 or by click chemistry. 48 Based on previous reports, we stated that dendronized malonic acid derivatives could enhance the aqueous solubility of fullerene C 60 by means of an amphiphilic system.…”
Section: Introductionmentioning
confidence: 99%
“…30–43 Polyester dendrimers and dendrons derived from 2,2′-bis(hydroxymethyl)propionic acid (bis-MPA) have gained singular attention related to their high aqueous solubility because of their hydroxyl groups in the periphery, that in turn, induced biocompatibility, and hydrolytic degradability. 44,45 These dendrons have used to enhance the aqueous solubility of curcumin by ester linkage 46,47 or by click chemistry. 48…”
Section: Introductionmentioning
confidence: 99%
“…6 Numerous approaches have been developed for efficient CCM delivery. In some cases, CCM derivatives were used to improve CCM performances; 7 in others, CCM or its derivatives have been loaded on other compounds such as polymers. For example, conjugation of CCM to poly(ethylene glycol) molecules by covalent bonds was reported by Safavy et al 8 to overcome the low aqueous solubility of CCM and improve its cytotoxic activity against some human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%